Poverty Curse Hypothesis of Resource-Rich Regions, a Development Paradox in Indonesia - Adi Wibowo, S; Susilo Parmansyah, P S (KnE Social Sciences, 2018)
This study aims to examine the hypothesis of natural resources curse in Indonesia in the era of regional autonomy. Poverty is the victim of an uncommon economic system within their limitations. Poor is a term that we often hear in everyday life. Poverty is usually connoted with a condition or state of being weak, deprived and vulnerable. The management of key resources, if properly managed will be a blessing, but if it does not really work it could be a curse. This research used the qualitative descriptive analysis method. The government is expected to re-examine the policies of natural resources related to the natural resources exploitations which are done massively in the era of regional autonomy. If the same condition persists, the massive exploitation of natural resources will only make Indonesia lose its natural resources that merely need a long time to recover, without getting the optimum advantages from the loss of natural resources. Keywords: Natural Resources Curse, Institution Quality, Economic Growth, and Poverty